"She encourages people to drink": A qualitative study of the use of females to promote beer in Nigerian institutions of learning##. (3rd July 2016) - Dumbili, Emeka W.
Abstract: Background : University students engage in heavy alcohol consumption and one factor that facilitates their alcohol use is alcohol marketing. Diverse sophisticated sales promotion strategies are used by multinational alcohol industries in Nigeria, and no policies to regulate alcohol promotion exist. This study explores the marketing strategy of using female students to promote beer in bars, nightclubs and hotels and how it facilitates alcohol use amongst students. Methods : Thirty-one in-depth interviews were conducted with university students (aged 19–23 years). The data were analysed to generate themes with the aid of NVivo 10 software (QSR International Pty Limited, Doncaster, Victoria, Australia). Results : The results show that female students identified as "beautiful" are strategically employed to promote beer brands in bars, nightclubs and other drinking sites. Beer promotion involves socialising in bars and persuading customers to buy more alcohol. Women agree to promote beer due to the commission that they are paid within a short time period. However, promoting beer creates different levels of risk for beer promoters. Beer promoters may be pressured into unwanted relationships because purchasing beer, for some men, constitutes the first step towards initiating a relationship with them. Their male customers are also at risk because they may drink large quantities of alcohol, either to gain the approval of a beer promoter in the hope of a relationship or to win prizes, such as free drinks and other branded paraphernalia that accompany beer promotion. Conclusions : The findings suggest that using women to promote beer facilitates their exploitation and also contributes to the growing alcohol-related problems in Nigeria. Effective written national alcohol control policies that regulate alcohol promotion should be formulated and implemented in Nigeria.